The Political Economy of Public Procurement Reform and Democratic Decentralisation in Indonesia - Mustafa, Mochamad (Indonesian Journal of Political Studies, 2021)
Procurement has been one of the most important areas of reform at both national and local levels since the fall of the New Order. This article provides an overview of procurement reform in Indonesia. This paper explains that following the implementation of democratic decentralization in 1999, the Indonesian government has embarked on efforts to ensure that Indonesian procurement procedures comply with international standards, particularly with regards to good governance and the competitiveness of public procurement. However, there is no substantial evidence that the implementation of procurement reform has resulted in more democratic procurement practices. Rather, the process of democratic decentralization has provided a political environment whereby the public procurement budget has become vulnerable to capture by predatory elites for their private interests, a process involving local politicians, local leaders, bureaucrats and business actors.